2009
DOI: 10.1111/j.1460-9568.2009.06837.x
|View full text |Cite
|
Sign up to set email alerts
|

Impulsive choice in hippocampal but not orbitofrontal cortex‐lesioned rats on a nonspatial decision‐making maze task

Abstract: Orbitofrontal cortical (OFC) and hippocampal (HPC) lesions in primates and rodents have been associated with impulsive behaviour. We showed previously that OFC- or HPC-lesioned rats chose the immediate low-reward (LR) option in preference to the delayed high-reward (HR) option, where LR and HR were associated with different spatial responses in a uniform grey T-maze. We now report that on a novel nonspatial T-maze task in which the HR and LR options are associated with patterned goal arms (black-and-white stri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
99
1
8

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(117 citation statements)
references
References 48 publications
(83 reference statements)
9
99
1
8
Order By: Relevance
“…Both lesions and inactivations of the OFC can have profound effects on choice behavior in delay-discounting tasks, with both increases and decreases in impulsive choice being reported (Mobini et al 2002;Rudebeck et al 2006;Winstanley et al 2004;Zeeb et al 2010; but see also Mariano et al 2009). Variation in the direction of the effects observed may reflect differences in the exact type of delay-discounting paradigm used, as well as differences in the basal level of impulsive choice exhibited, which ultimately can change the manner in which the OFC is recruited into the decision-making process (Mariano et al 2009;Winstanley 2010;. Nevertheless, there is a general consensus that activity within the OFC can critically modulate this form of impulsivity, largely due to the important role of this region in generating outcome expectancies (Mariano et al 2009;Roesch et al 2007;Zeeb et al 2010).…”
Section: Discussionmentioning
confidence: 95%
“…Both lesions and inactivations of the OFC can have profound effects on choice behavior in delay-discounting tasks, with both increases and decreases in impulsive choice being reported (Mobini et al 2002;Rudebeck et al 2006;Winstanley et al 2004;Zeeb et al 2010; but see also Mariano et al 2009). Variation in the direction of the effects observed may reflect differences in the exact type of delay-discounting paradigm used, as well as differences in the basal level of impulsive choice exhibited, which ultimately can change the manner in which the OFC is recruited into the decision-making process (Mariano et al 2009;Winstanley 2010;. Nevertheless, there is a general consensus that activity within the OFC can critically modulate this form of impulsivity, largely due to the important role of this region in generating outcome expectancies (Mariano et al 2009;Roesch et al 2007;Zeeb et al 2010).…”
Section: Discussionmentioning
confidence: 95%
“…Hippocampal lesions have well-documented effects on spatial memory tasks, but alongside these there are numerous examples of hippocampal lesions also affecting non-spatial memory tasks [74][75][76][77][78][79] . Furthermore, there is considerable evidence that the hippocampus plays a role beyond the memory domain altogether.…”
Section: Beyond the Spatial Memory Domainmentioning
confidence: 99%
“…McHugh and colleagues [35] have shown, using a spatial task involving a choice between a delayed-larger vs. an immediate-small rewards, that both OFC-or HPC-lesioned rats showed an increase in impulsive choice. Interestingly, the same group [34] recently reported that, using a non-spatial version of the same task, HPC-lesioned rats exhibited impulsive choice whilst OFC-lesioned rats did not. Thus, the role of OFC in choice with delayed rewards could be more limited [61], and that of the HPC more extensive, than classically thought; this is probably related to HPC role in temporal information processing [34,61].…”
Section: Cognitive Impulsivitymentioning
confidence: 99%
“…Interestingly, the same group [34] recently reported that, using a non-spatial version of the same task, HPC-lesioned rats exhibited impulsive choice whilst OFC-lesioned rats did not. Thus, the role of OFC in choice with delayed rewards could be more limited [61], and that of the HPC more extensive, than classically thought; this is probably related to HPC role in temporal information processing [34,61]. We may conclude that the transient increase in choice for a delayed reward, exhibited by Lenti-SERT, supports the hypothesis of an inverse relationship between 5-HT and impulsivity [55], being consistent with available data both on 5-HT manipulations (including pathway lesions, SSRI administration and SERT knockout) and HPC lesions.…”
Section: Cognitive Impulsivitymentioning
confidence: 99%